Influence of Contextual, Developmental, and Demographic Variables on Social Activism Among Undergraduates in Sri Lankan Universities - Abeysinghe, Nisshankage Shantha (2009)
Engagement in social activism is one of the means for building identity and citizenship competencies of young people. On campus, one of the vehicles that provide engagement in social activism is the students’ union. In Sri Lankan campuses the students’ union system has been established by the University Act and it has accorded the Student Unions with a wider scope for the engagement in such activities. Sri Lankan campus youth are encouraged to engage in both internal and external socio economic and welfare issues and to voice for the betterment of both campus youth and the public at large. Therefore a study that aims to measure the important determinants of youth’s contribution relating to the engagement in social activism, should essentially take into consideration the related developmental as well as contextual variables. The specific objectives of the study were to determine the level of social activism of campus youth, the level of social activism across selected contextual variables and demographic variables and the relationships between the level of social activism and the selected contextual variables and developmental variables. Finally, the contribution made by the selected demographic, developmental, and contextual factors on social activism was examined. Four hundred and forty nine subjects were randomly selected from six campuses and representing three faculties (Science, Arts & Commerce/Management). The findings showed that the developmental variables such as self esteem, aggression and impression on governance were significantly related to the social activism of youth. Similarly, contextual variables namely, school extra curricular activities, campus club engagement and gender as a demographic variable was significantly related to social activism. Even though social activism among campus youth was high, an important feature within this observed phenomenon was the gender segregation. Female voice was not significantly represented in the context of contemporary social activism among campus youth. Subsequently, seniority in terms of age as well as the number of years stayed at the campus enhances the level of engagement in social activism. The level of self esteem, impression on governance, parents’ income and female composition at campuses negatively effect the engagement in social activism. The conceptual model developed for this study was able to explain the factors influencing social activism among campus youth. Accordingly, the influence of the contextual factors on the engagement with social activism was greater than the influence of the developmental factors. Hence, external factors (contextual and demographic) have greater influence on the level of engagement in social activism than internal (Developmental) factors. Policy recommendations for positive youth development are discussed with special attention to minimizing aggressive nature of social activism and building a harmonious democratic culture among youth at the higher educational institutions.